2013
DOI: 10.1016/j.joca.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy is activated in compression-induced cell degeneration and is mediated by reactive oxygen species in nucleus pulposus cells exposed to compression

Abstract: Enhanced degradation of damaged components of NP cells by autophagy may be a crucial survival response against mechanical overload, and extensive autophagy may trigger autophagic cell death. Regulating autophagy and reducing the generation of intracellular ROS may retard IVD degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
121
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(131 citation statements)
references
References 41 publications
8
121
0
Order By: Relevance
“…Although the causative relationship between disc degeneration and autophagy is not yet clear, alterations in the level of autophagy have been observed in degenerated IVDs, IVDs of aged or diabetic rats [37][38][39] and NP cells derived from degenerative human discs. 40 In addition, various stresses such as high glucose, 41,42 aberrant mechanical compression, 43 lactate overload, 44 glucosamine, 45 and reactive oxygen species (ROS), 43 activate autophagy in NP cells, further implicating autophagy modulation as a possible contributor to disc pathologies. However, studies investigating the mechanisms of how basal autophagy is controlled in NP cells and the role of physiological stimuli in this process are mostly lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Although the causative relationship between disc degeneration and autophagy is not yet clear, alterations in the level of autophagy have been observed in degenerated IVDs, IVDs of aged or diabetic rats [37][38][39] and NP cells derived from degenerative human discs. 40 In addition, various stresses such as high glucose, 41,42 aberrant mechanical compression, 43 lactate overload, 44 glucosamine, 45 and reactive oxygen species (ROS), 43 activate autophagy in NP cells, further implicating autophagy modulation as a possible contributor to disc pathologies. However, studies investigating the mechanisms of how basal autophagy is controlled in NP cells and the role of physiological stimuli in this process are mostly lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Hostile environments induce cells to upregulate autophagy to remove toxic protein aggregates and provide amino acids and fatty acids. It has also been suggested that autophagy plays a role in the onset of IDD and that controlling the autophagy response in NP cells under oxidative stress should be beneficial for the survival of the cells and would likely delay the process of disc degeneration [2, 51-53]. …”
Section: Discussionmentioning
confidence: 99%
“…Ma et al (110) found that autophagy triggered by compression in rat NP cells was associated with apoptosis and intracellular ROS production. However, elucidation of the exact role of autophagy and the precise mechanism mediating autophagy activation require further investigation.…”
Section: Mechanical Stressmentioning
confidence: 99%